Predictors of Endovascular Treatment Among Stroke Codes Activated Within 6 Hours From Symptom Onset. Issue 9 (September 2018) - Requena, Manuel; Pérez de la Ossa, Natalia; Abilleira, Sonia; Cardona, Pere; Urra, Xabier; Martí-Fabregas, Joan; Rodríguez-Campello, Anna; Boned, Sandra; Rubiera, Marta; Tomasello, Alejandro; Molina, Carlos A.; Ribo, Marc
Abstract : Background and Purpose—: Prehospital stroke code activations help reducing workflow times during in-hospital triage. We aim to identify predictors of endovascular treatment (EVT) among stroke codes (SC) activated within 6 hours from symptom onset. Methods—: CICAT (Codi Ictus Catalunya) is a prospective official mandatory registry of all SC in Catalunya. We studied all CICAT entries from 6 comprehensive stroke centers for 18 months. We recorded demographic, clinical, and imaging variables on admission. We explored the relationship between these variables and EVT Results—: From 3944 SC, 2778 (70.4%) were admitted within 6 hours from symptom onset. Mean age was 72±15.3 years, median Rapid Arterial Occlusion Evaluation scale score 4 (interquartile range [IQR], 2–6), median onset-to-door time 89 minutes (IQR, 54–158), median National Institutes of Health Stroke Scale score 9 (IQR, 4–18), median Alberta Stroke Program Early CT Score 10 (IQR, 8–10). Final diagnosis was ischemic stroke in 1762 patients (63.4%), hemorrhagic stroke in 359 (13.0%), transient ischemic attack in 164 (5.9%), and stroke-mimic in 493 (17.7%). A large vessel occlusion was confirmed in 720 (25.6%) patients. Of all SC, 16% (n=444) received EVT, with a median door-to-groin time of 77 minutes (IQR, 55–102). Baseline variables associated with EVT were premorbid modified Rankin Scale score <2 ( P <0.001), prehospital Rapid Arterial Occlusion Evaluation scale score >4 ( P =0.003), and National Institutes of Health Stroke Scale on admission >8 ( P <0.001). National Institutes of Health Stroke Scale on admission was the only independent predictor of EVT. Although the rate of Alberta Stroke Program Early CT Score 10 progressively decreased over time (0–3 hours, 73.2% versus 3–6 hours, 57.1%; P <0.01), the rate of Alberta Stroke Program Early CT Score 6 remained >90% along time (0–3 hours, 95.1% versus 3–6 hours, 94.0%; P =0.25) and did not decrease over time. The chances to receive EVT and the presence of large vessel occlusion decreased over time. However, the rate of EVT was not different between patients admitted 0 to 3 hours (26.1%) and those admitted 3 to 6 hours (22.9%; P =0.2). Conclusions—: Among SC within 6 hours from symptom onset, National Institutes of Health Stroke Scale on admission was the only factor independently associated with EVT. Only 5% of these patients show an Alberta Stroke Program Early CT Score <6 and this rate does not significantly increase over time. These data may be useful to generate direct transfer to angio-suite protocols based mainly on clinical severity.